The Illocutionary Acts in X Social Media Platform: “Hold On, It Hurts,” an Indonesian Alternative Universe (AU) by Noveni Adelia - Agus Darma Yoga Pratama (The Doctoral Studies Program of Linguistics of Udayana University, 2024)
This article explores illocutionary acts within the